Reconstruction - Howse, Jennifer (Black history (Smartbook Media Inc.), 2020)
Traces the history of Reconstruction from 1866 to 1876, highlighting notable events and people, and discussing how it changed America and the lives of African Americans. Features photographs, fact boxes, a timeline, an activity, a quiz, and a glossary.